2018
DOI: 10.3390/vetsci5030062
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro Antimicrobial Efficacy of Sixteen Essential Oils against Escherichia coli and Aspergillus fumigatus Isolated from Poultry

Abstract: Escherichia coli and Aspergillus fumigatus are two pathogens largely present among poultry. They can cause mild or severe forms of disease, and are associated with significant economic losses. The aim of the present study was to investigate the chemical composition and the in vitro antimicrobial activity of sixteen essential oils (EOs) and five mixtures against E. coli and A. fumigatus strains previously isolated from poultry. The study was performed with the following EOs: Aloysia tryphilla, Boswellia sacra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 34 publications
4
50
1
2
Order By: Relevance
“…isolated from human patients, with MIC values higher (35-140 mg/mL) than the value observed in the present study. Moreover, this EO showed a good activity against Aspergillus fumigatus in a previous study [49] and a poor effectiveness versus the probiotic yeast Saccharomyces cerevisiae [50], indicating a variable efficacy against different species of both molds and yeasts. The antifungal activity seems to be related to a higher content of limonene and sabinene, in comparison with the other EOs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…isolated from human patients, with MIC values higher (35-140 mg/mL) than the value observed in the present study. Moreover, this EO showed a good activity against Aspergillus fumigatus in a previous study [49] and a poor effectiveness versus the probiotic yeast Saccharomyces cerevisiae [50], indicating a variable efficacy against different species of both molds and yeasts. The antifungal activity seems to be related to a higher content of limonene and sabinene, in comparison with the other EOs.…”
Section: Discussionmentioning
confidence: 71%
“…These results are in agreement with findings reported by Bismarck et al [52] and Sim et al [56] in otologic canine isolates. This EO, in fact, although poorly effective against molds such as A. fumigatus [49] and dermatophytes [55], showed a strong antimicrobial activity versus Salmonella enterica serotype Typhimurium and Escherichia coli isolated from poultry [50].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that bergamot was effective against E. faecalis, with MICs of 219.25 mg/ml for the pure essential oil and of 169.5 mg/ml for the combination with calcium hydroxide. e few studies on the antimicrobial activity of bergamot were unable to demonstrate effectiveness against microorganisms such as E. coli [29]. Mixtures of different essential oils were also tested, but they were only effective at a very high concentration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Seu uso comercial baseia-se principalmente em preparações para o chá e ainda a utilização de substâncias extraídas da planta, especialmente do óleo essencial, utilizado na indústria de alimentos e cosméticos (DUBEY et al, 1997). O chá do capim cidreira é indicado popularmente para o stress, dor, febre, tosse e alterações digestivas, sendo que constituintes extraídos do óleo essencial da planta demonstra efeitos antiespasmódico, antibacteriano, analgésico (COSTA et al, 2005;EKPENYONG, 2015;EBANI, 2018), fungicida (ALMEIDA et al 2008;BOUKHATEM, 2014), ansiolítica e sedativa (BLANCO et al 2009).…”
Section: Introductionunclassified